Effect of Heat Treatment on the Microstructure and Hardness of Low-Alloy Carbon Steel Used in Structural Applications - Teba Ahmed (Indonesian Journal Publisher, 2026)
This research was conducted to evaluate the effects of various heat treatment methods on the microstructure and mechanical properties of low alloy carbon steel used in structural applications. The laboratory samples underwent a series of annealing, normalizing, quenching, and tempering processes, leading to the development of fine grains within specific temperatures of the austenitic range. The holding time for uniform temperature distribution was maintained by subsequent cooling rates through air, oil, and water quenching. An optical microscope showed substantial variations in the shapes of ferrite and pearlite, whereas a SEM could see the shape of martensite, depending on how it was treated. Mechanical tests, including the Vickers hardness test and the tensile strength test, were conducted to correlate the development or change in properties. The highest hardness is reported owing to the production of quenched samples, which is explained by tempering ductile materials to make them less brittle. Provided normalized showed balanced and appropriate for both needed use The research includes useful data that engineers may use to improve the performance of building materials that are exposed to changing load situations by changing the parameters of heat treatment. This, therefore, gives a good reason to choose the right way to heat treat low-alloy steels to get the needed mechanical qualities.